Implementasi Pembelajaran Variatif dalam Pendidikan Islam: Solusi Terhadap Tantangan Pemahaman Mahasiswa - Azmi, Muhammad (Program Studi Pendidikan Agama Islam, 2025)
Islamic Religious Education is an important component in the formation of character and morals of students in higher education. However, students' understanding of the concept of Islamic religious education still faces various obstacles influenced by the learning methods applied. This study aims to evaluate the implementation of learning methods and their impact on students' understanding of the concept of Islamic Religious Education. The research method uses a qualitative approach with data collection techniques in the form of in-depth interviews with a number of students taking the Islamic Religious Education course. Data analysis was carried out thematically to identify obstacles and the effectiveness of the learning methods used. The results of the study showed variations in students' understanding influenced by the type of learning method, where interactive methods such as group discussions and project-based learning were more effective in increasing understanding than traditional lecture methods. The obstacles encountered included social environmental pressure, lack of practical understanding, limited time management, and the influence of a modern lifestyle that did not support the practice of religious values. The role of lecturers as facilitators and role models is very influential in increasing students' motivation to learn and practice religious values. Therefore, the implementation of varied and contextual learning methods is very important in helping students understand and internalize the concept of Islamic Religious Education. This study emphasizes the need for the development of innovative learning methods and the provision of conducive learning environment support to improve the effectiveness of religious education in higher education.